2020
DOI: 10.21037/acs-2020-surd-17
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve replacement using stented or sutureless/rapid deployment prosthesis via either full-sternotomy or a minimally invasive approach: a network meta-analysis

Abstract: Background: New technologies such as sutureless or rapid deployment prosthetic valves and access via minimally invasive incisions offer alternatives to traditional full-sternotomy aortic valve replacement (SAVR). However, a comprehensive comparison of these surgical techniques along with alternative valve prosthesis has not been completed. Methods: Electronic databases were searched for studies comparing outcomes for SAVR, minimally invasive AVR (MiAVR), sutureless/rapid-deployment AVR (SuAVR) via full-sternot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…8 Minimally invasive SAVR, performed via upper hemisternotomy or right anterior thoracotomy, may reduce postoperative pain length of stay, and improve patient cosmesis compared to SAVR via median sternotomy, with similar rates of mortality and stroke. 57…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Minimally invasive SAVR, performed via upper hemisternotomy or right anterior thoracotomy, may reduce postoperative pain length of stay, and improve patient cosmesis compared to SAVR via median sternotomy, with similar rates of mortality and stroke. 57…”
Section: Discussionmentioning
confidence: 99%
“…8 Minimally invasive SAVR, performed via upper hemisternotomy or right anterior thoracotomy, may reduce postoperative pain length of stay, and improve patient cosmesis compared to SAVR via median sternotomy, with similar rates of mortality and stroke. 57 Therefore, the SAVR versus TAVR comparison, in the broad sense, comes from the clinical trials as summarized in this review. The SAVR versus TAVR team recommendation for the individual patient, and the subsequent patient choice, has multiple dimensions.…”
Section: Areas Of Uncertainty and Consensus Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] Studies have also shown mis-AVR results in less blood transfusion, shorter assisted ventilatory time, lower stroke rates, and fewer patients with postoperative atrial fibrillation (AF). [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Sternum-sparing RAMT may be the optimal mis-AVR approach, with benefits of even less AF and shorter hospital stay when compared to upper hemisternotomy. 29 With demonstrated safety and favorable clinical outcomes, including patient satisfaction, the RAMT approach was incorporated into our minimally invasive valve surgery program in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that, when compared to sAVR, mis‐AVR is associated with better clinical outcomes, including reduced postoperative mortality and morbidity, shorter hospitalization, improved renal and pulmonary function, and reduced wound infection rates 15–21 . Studies have also shown mis‐AVR results in less blood transfusion, shorter assisted ventilatory time, lower stroke rates, and fewer patients with postoperative atrial fibrillation (AF) 19–33 …”
Section: Introductionmentioning
confidence: 99%
“…to conventional sutured AVR in patients presenting with severe aortic valve disease 1 . Current SURD valve technologies were introduced about 15 years ago to reduce operative times and facilitate minimally invasive techniques 2,3 . Additionally, SURD-AVR demonstrated to improve valve hemodynamic and facilitate valve prosthesis implantation in challenging anatomical settings 4,5 .…”
mentioning
confidence: 99%